Multitraits evaluation of Pakistani ecotypes of berseem clover (Trifolium alexandrinum L.) under full-irrigation and water restriction conditions - Hussain, M.M.; Rauf, S.; Paderewski, J.; Ulhaq, I.; Sienkiewicz-Paderewska, D.; Monneveux, P. (2015)
Berseem clover (Trifolium alexandrinum L.) is an important forage crop in Pakistan and many ecotypes are grown across the country. Its yield is however frequently affected by insufficient irrigation due to unavailability of water. In the present study, twenty Pakistani ecotypes of berseem clover have been evaluated in lysimeters under full irrigation and water restriction conditions. In the full irrigation treatment soil humidity was maintained at field capacity, while in the water restriction treatment water was only supplied after severe wilting and to maintain humidity in the deep profile of the soil. Assessed traits included forage yield, calculated as the sum of the biomass harvested at 70 and 110 DA days after emergence, and morpho-physiological traits. Significant effects of water restriction were noted on yield, leaf gas exchange parameters, canopy temperature and osmotic adjustment. Most morpho-physiological traits had higher broad sense heritability than forage yield, both under full irrigation and water restriction conditions. Water restriction increased genetic and phenotypic variability and heritability of most traits under study. Under these conditions forage yield was positively associated to leaf temperature and recovery rate index and, under full irrigation, to net photosynthetic rate, canopy depression temperature and leaf area. The possible use of these traits as indirect selection criteria in berseem clover breeding programs is discussed. Some ecotypes with favorable traits such as high forage yield potential, good adaptation to water restriction and aptitude to multiple harvesting have also been identified.